ON THE IMPOSSIBILITY OF MEASURING THE GENERAL RELATIVISTIC PART OF THE TERRESTRIAL ACCELERATION OF GRAVITY WITH SUPERCONDUCTING GRAVIMETERS - Iorio L. (My University, 2006)
In this paper we very preliminarily investigate the possibility of measuring the post-Newtonian general relativistic gravitoelectric and gravitomagnetic components of the acceleration of gravity on the Earth, in continuous regime, with two absolute measurements at the equator and the South Pole with superconducting gravimeters. The magnitudes of such relativistic effects are 10-10 m s-2 and 10-11 m s-2, respectively. Unfortunately, the present-day uncertainties in the Earth's geodetic parameters, which enter the classical Newtonian terms induce systematic errors that are one to two orders of magnitude larger than the relativistic ones. Moreover, a ~1 ngal sensitivity can be reached by the currently available superconducting gravimeters, but only for relative measurements. © 2006 The Author Journal compilation © 2006 RAS.
Keywords: EARTH-BASED EXPERIMENTS; POST-NEWTONIAN GRAVITY; SUPERCONDUCTING GRAVIMETERS